Design of Data Interchange Regulation for Regional ICT Office - Falahah, -; Santoso, Ari Fajar (JOIV : International Journal on Informatics Visualization, 2022)
The rapid development of e-government systems raises issues of the importance of data integration and interoperability. Recently, most government offices provide data interchange services through web services or using database direct-link (db-link), and the process usually runs without referring to certain regulations, standards, or procedures.  It can cause some problems such as lack of a standard for data interchange services, lack of procedure for building, deploying, and monitoring the services, duplicate services, problems in tracing and maintaining the services, and much more.  The research aims to provide the practical method for designing the regulation for supporting data interchange and propose a draft of the regulation package that consists of policy, procedure, and technical guide.  The research is located in a regional ICT government office and the process for designing the regulation is building through a design thinking approach. Outputs of this research are the conceptual map of the issues that should be covered by the regulation, the structure of the policy, the draft of standard and procedure for supporting data interchange mechanism, and the sample of the technical guide. The draft of the regulation is then tested against the actual problem to see how the regulation, procedure, and guide can resolve it.  The result shows that it can fill the needs of regulation in the organization and can address some needs on data interchange mechanisms.